Paper Waste Hydrolysis with Stepwise Sulfuric Acid Catalyst - Panjaitan, Jabosar Ronggur Hamonangan; Nury, Dennis Farina; Hutabarat, Fransisco Xala; Hutabarat, Monalisa (Universitas Tribhuwana Tunggadewi Malang, 2023)
The need for paper results in a lot of paper waste. Paper waste, which is lignocellulosic, can be hydrolyzed using an acid catalyst to produce various cellulose degradation products. In this study, the effect of the sulfuric acid catalyst addition method on the waste paper hydrolysis process was investigated. The addition of the catalyst was carried out in three types. The Type-1 method was sulfuric acid addition in the 0th minute. The Type-2 method was sulfuric acid addition in the 0th and 30th minutes. The Type-3 method was sulfuric acid addition every 10 minutes. The results showed that the lowest residual mass of waste paper hydrolyzed was produced using the Type-3 method. This showed that the Type-3 method, sulfuric acid addition every 10 minutes, had an effect on the residual mass of the hydrolyzed sample. The Type-3 method was the most effective type of sulfuric acid catalyst addition compared to other types. On the other hand, variations in the concentration of the sulfuric acid catalyst affect the residual mass of the waste paper hydrolyzed sample, where higher sulfuric acid concentration will lower residual mass. The catalyst concentration of 2% sulfuric acid with The Type-3 addition method resulted in the highest conversion which was 38.27%.